СОВРЕМЕННЫЕ ПОДХОДЫ К ДИАГНОСТИКЕ И ЛЕЧЕНИЮ АЛЛЕРГИЧЕСКОГО РИНИТА.ОБЗОР ЛИТЕРАТУРЫ («Наука и здравоохранение», 2026)
The important prophylactic is timely diagnosis of allergic rhino sinusitis. Corticosteroids for local application should beused at the easy and average form of seasonal allergic rhinitis’s.